Usaha Pengolahan Ikan dan Cacing Laut (Kian) Asap di Ohoi Wab, Kecamatan Hoat Sorbay - Daniel Ngabalin; Eygner Gerald Talakua (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Smoked fish processing business in Wab Village still used traditional methods (fumigation open) and are household enterprises (micro-scale enterprises) can be seen from the aspect of production and management aspects. Two aspects of this raise the priority issues faced by partners namely: how the fish correct fumigation techniques? What forms fumigation appropriate tool? How to manage capital and production business properly? How do I do the recording business activities in the notebook business correctly? And how to sell or market products correctly? Through methods of participatory rural appraisal, fisheries extension method, and the method pretest-posttest control group design, the implementation of community service activities carried out as a priority the settlement solution problem by doing: 1) Initial extension of community service activities; 2) Extension of heat curing, heat curing tool making appropriate, and the use of heat curing; 3) Counseling on capital management and production; 4) Extension of book production business records; and 5) Counseling about pricing, promotion, and strategy for dealing with the business of competition. So the outcome reached was contained fish products and marine worms (increasingly) the smoke as much as 25 / week; there are two tools used fumigation partners; there were five notebooks submitted to partners and capable of recording the three notebooks (book purchases, sales, and profit/loss); and 50 fish and marine worms (increasingly) smoke marketed in Wab Village.